Hemispheric Imaginings : The Monroe Doctrine and Narratives of U.S. Empire - Murphy, Gretchen, 1971- (Book collections on Project MUSE., 2005)
Examines the key role that the spatial construct (embodied by the Monroe Doctrine) of the western hemisphere played in enabling and effacing U.S. empire.